Phenotypic, genetic, and transcriptomic decoupling of thermal hardiness across metamorphosis in Drosophila melanogaster - Freda, Philip John (Kansas State University, 2018)
Complex life cycles (CLCs), developmental programs in which life-history stages are distinct in morphology, behavior, and physiology, are common throughout the biosphere. However, it is still unclear why and how CLCs evolve. The adaptive decoupling hypothesis (ADH) postulates that CLCs evolve to decouple the developmental processes that underlie traits across ontogeny to allow for independent, stage-specific responses to selection. This ultimately could lead to alternate life-history stages adapting to unique environments, thus optimizing fitness across development. However, few empirical tests of the ADH are available. Detecting genetic and transcriptomic decoupling of thermal hardiness using robust techniques in a model system, D. melanogaster, was the goal of this dissertation. Furthermore, this work illustrates that different life-history stages have the potential to become adapted to unique ecological niches. I performed three primary studies to test the ADH: 1.) estimation of the genetic correlation for cold hardiness between larvae and adults using isogenic lines of D. melanogaster to determine if unique genetic architectures underlie variation in cold stress response using standard quantitative genetic and Genome-Wide Association (GWA) methods, 2.) testing whether developmental acclimation is genetically correlated across stages, and whether acclimation alters cross-stage correlations in cold hardiness, and 3.) analysis of the transcriptional responses of both larvae and adults to extreme cold to determine if stage-specific stress response mechanisms exist across development.
Keywords: Drosophila; metamorphosis; decoupling; genetic; transcriptomic; phenotypic